2021
DOI: 10.3390/life11111169
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of the Lipoxygenase Gene Family to Salt and Drought Stress in Foxtail Millet (Setaria italica)

Abstract: Plant lipoxygenases (LOXs), a kind of non-heme iron-containing dioxygenases, participate plant physiological activities (especially in response to biotic and abiotic stresses) through oxidizing various lipids. However, there was few investigations on LOXs in foxtail millet (Setaria italica). In this study, we identified the LOX gene family in foxtail millet, and divided the total 12 members into three sub-families on the basis of their phylogenetic relationships. Under salt and drought stress, LOX genes showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…(Seita.4G273900) were also detected to be involved in the salt stress response of foxtail millet in previous studies (Puranik et al, 2011;Liu et al, 2016;Zhang et al, 2021). In addition to foxtail millet, these genes were also identified in plant abiotic stress responses in other species.…”
Section: Prediction Of Drought Stress Response Degsmentioning
confidence: 76%
See 2 more Smart Citations
“…(Seita.4G273900) were also detected to be involved in the salt stress response of foxtail millet in previous studies (Puranik et al, 2011;Liu et al, 2016;Zhang et al, 2021). In addition to foxtail millet, these genes were also identified in plant abiotic stress responses in other species.…”
Section: Prediction Of Drought Stress Response Degsmentioning
confidence: 76%
“…This study identified 46 genes whose expression levels changed regularly in JiguX/Jigu, JinguX/Jingu, and LongguX/Longgu (Table 2). In previous studies, Seita.2G141500 (Zhang et al, 2022), Seita.1G239600, Seita.5G022000, Seita.9G379000 (Shi et al, 2018), Seita.1G326200, Seita.5G294000, Seita.7G045200 (Qin et al, 2020), Seita.1G349800 (Zhao et al, 2021), Seita.5G393800 (Liu et al, 2016), and Seita.7G113700 (Zhang et al, 2021) have been identified to play an important role in the drought process of foxtail millet. In addition, SiBZIP12 (Seita.5G393800), SiPP2C50 (Seita.5G294000), SiSAPK1…”
Section: Prediction Of Drought Stress Response Degsmentioning
confidence: 95%
See 1 more Smart Citation
“…This study adds Cannabaceae to the collection of plant families with described LOX gene families, a group which so far includes Aracae: duckweed (102); Actinidiaceae: kiwi (103); Brassicaceae: Arabidopsis thaliana (104106), radish (107), and turnip (108); Caricaceae: papaya (106); Cucurbitaceae: cucumber (109, 110), melon (111), and watermelon (112); Fabaceae: Medicago truncatula, peanut (113), and soybean (114); Malvaceae: cotton (115) Muscacea: banana (116); Poaceae: maize (117), rice (105), Setaria italica (118), sorghum (119); Polygonaceae: buckwheat (120); Rhamnaceae: Jujubie (121); Rosaceae: apple (122), peach (123), pear (124); Salicaceae: poplar (125); Solanaceae: pepper (126) and tomato (127, 128); Theaceae: Camellia sinensis (129); and Vitaceae: grape (130).…”
Section: Discussionmentioning
confidence: 99%
“…Increased mRNA levels of the PLD gene and activity of PLD was observed in A. thaliana [27], sweet orange [28], Craterostigma plantagineum [29], Petunia [7], Vigna radiata [30], Z. mays [31], and Arachis hypogaea [32] under drought. In turn, accumulation of LOX mRNA evoked by water deficit has been demonstrated in Capsicum annuum L. [33], P. vulgaris [34], Panax ginseng [35], Diospyros kaki [36], Setaria italica [37], Cucumis melo [38], Solanum lycopersicum [39], Agrostis stolonifera [40], and Triticum aestivum [41]. LOX-encoding lipoxygenases catalyze the conversion of α-linolenic acid to (13S)-hydroperoxy-octadecatrienoic acid (13-HPOT), which is further subjected to processes of oxidation, cyclization, and acyl chain shortening, to finally form JA [42,43].…”
Section: Introductionmentioning
confidence: 99%